Upaya Meningkatkan Kemampuan Meringkas Cerita Ramayana melalui Pagelaran Ketoprak dengan Metode Pembelajaran Kooperatif - M. Mujib (CV. Pusdikra Mitra Jaya, 2023)
The purpose of writing this article is to describe the results of classroom action research on efforts to improve the ability to summarize the Ramayana story through ketoprak performances using cooperative learning methods. The research sample was grade VIII students of MTS N 1 Pati. Collecting data using observation methods, learning achievement tests and questionnaires. Quantitative and qualitative data analysis techniques. The results showed that students' ability to summarize the Ramayana story could be increased through ketoprak performances using cooperative learning methods.